Guar root and shoot growth as affected by soil compaction - Bassegio, Doglas; Mansano Sarto, Marcos Vinicius; Rosolem, Ciro Antonio [UNESP]; Wobeto Sarto, Jaqueline Rocha [UNESP] (Univ Federal Goias, 2018)
Guar (Cyamopsis tetragonoloba L.) is commonly grown in arid lands, because of its high drought-tolerance. However, soil compaction may be a limiting factor to its growth. This study aimed to evaluate the guar growth, according to the soil penetration resistance (0.20 MPa, 0.33 MPa, 0.50 MPa, 0.93 MPa and 1.77 MPa, in a layer with depth between 0.15 m and 0.20 m), in a Rhodic Acrudox soil. The shoot and root dry mass, root length by the Q(1/2 )index (mechanical soil penetration resistance in which the root growth is reduced by 50 %) and root diameter were evaluated. The impairment of the guar shoot growth begins when the penetration resistance is greater than around 1 MPa. The soil compaction alters the distribution of guar roots in the soil profile, concentrating them in the 0.15 m layer, but it does not prevent roots from penetrating this layer and developing in depth. The root diameter increases in the compacted layer. A soil penetration resistance of up to 1.77 MPa does not influence the root length density below the compacted layer, as well as the total root length density of guar. Although the guar Q(1/2) index is greater than 1.58, the shoot and root dry mass are impaired.